2020
DOI: 10.4187/respcare.07098
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training in COPD

Abstract: BACKGROUND: The benefits of inspiratory muscle training (IMT) for patients with COPD are documented in the literature, but its isolated effect or association with other interventions, the best training methods, and what type of patient benefits the most are not clear. We sought to assess the effects of IMT on respiratory muscle strength, pulmonary function, dyspnea, functional capacity, and quality of life for subjects with COPD, considering IMT isolated or association with other interventions, presence of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 73 publications
1
31
0
3
Order By: Relevance
“…EMST has been reported as beneficial for improving hyolaryngeal excursion and decreased penetration-aspiration, in some studies, as well as improving cough—important for effective airway clearance. 37 IMST increases inspiratory muscle strength in PwCOPD resulting in increased inspiratory volume capacity, 38 but to our knowledge, the impact of IMST on swallowing in this patient group is not yet understood. Respiratory–swallow patterning is the only intervention known to have positive outcomes specific to PwCOPD with dysphagia-embedded within a study examining head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…EMST has been reported as beneficial for improving hyolaryngeal excursion and decreased penetration-aspiration, in some studies, as well as improving cough—important for effective airway clearance. 37 IMST increases inspiratory muscle strength in PwCOPD resulting in increased inspiratory volume capacity, 38 but to our knowledge, the impact of IMST on swallowing in this patient group is not yet understood. Respiratory–swallow patterning is the only intervention known to have positive outcomes specific to PwCOPD with dysphagia-embedded within a study examining head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, we found that the decreases of CAT score and mMRC score were larger in patients with FEV1 < 30%, although it did not reach the statistical difference, which may owe to the small case numbers in the FEV1 < 30% group. A recent meta-analysis demonstrated the benefit of IMT in improving COPD parameters; the authors reported that a shorter intervention time (≤4 weeks) improved MIP only, and a longer training period (6–8 weeks) also improved functional capacity, such as 6MWT distance [ 45 ]. Although the training period of our study was up to 8 weeks, no significant change was found in the 6MWT distance.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory muscle training has been extensively studied because of its recognized effects. [51][52][53] Xia et al 54 reported that respiratory muscle training improves diaphragmatic dysfunction in patients with COPD. Respiratory muscle training methods, such as resistance loading method, pressure threshold loading method, and carbon dioxide hyperventilation method, have been used to delay the weakening of diaphragmatic contractile function, improve pulmonary function, and enhance quality of life.…”
Section: Diaphragmatic Breathing Trainingmentioning
confidence: 99%